Taxation in European Union - Boria, Pietro (Springer, 2017)
The “European tax law” is a set of regulations issued by the EU institutions and designed to provide the control of tax matters over the tax legislations of the Member States. However, the existence of EU rules aimed to regulate the procedures for taxation in the European Member States is not enough to identify an area of an independent and autonomous law. In fact, if the tendency to profile the EU law is developing in the recent times, in order to valorize the regulatory provisions of specific areas of the legal system (giving a meaning to the definition of “European private law” or “European administrative law” or even “European trial law”), it must be considered that the identification of an autonomous sector of law requires the logic of a “legal system”; it basically implies the existence of principles and juridical values and the dynamic relationships between the norms. Therefore, the existence of a set of general rules by EU institutions cannot be considered sufficient to identify a “European tax law”; if these rules compose a mere aggregate without a functional meaning, the element of the systematic unity would be lacking and there should not be an autonomous order of law. In any case, there are several elements which lead to identify an independent and autonomous sector of law in the set of EU norms regarding the taxation law. First of all, specific and peculiar sources of EU law may be detected, which clearly express the capacity of the European institutions to proceed independently in the regulation of tax laws over the legislative powers of the Member States. Moreover, several principles, which are intended to set the basic values of the taxation procedure, would be defined at a primary axiological level and specifically in the Treaty of the European Union. Without anticipating topics that will be developed during this work, some juridical values may be certainly stated as the main guidelines of EU regulation: the removal of customs barriers, the protection of the fundamental economic freedoms in the common market, the principle of fiscal non-discrimination, the prohibition of the State aids, the preservation of national public finances and the tax harmonization.